Identifying future risks to UK agricultural crop production: Putting climate change in context - Knox, Jerry W.; Morris, Joe; Hess, Tim M. (Ip Publishing, 2010)
Internationally, agriculture is widely regarded as one of the sectors at most risk from a changing climate. This is due to the impact of increased temperatures, reduced rainfall and increased frequency of extreme events, not only in the tropics but also in temperate environments. In the UK, growers also face a range of 'non-climate' risks, which, it is often argued, present a potentially greater and more immediate threat to sustainable food production than climate change. This paper highlights the climate and non-climate impacts on crop production, the adaptation options and the institutional and regulatory barriers to their uptake by farmers. It concludes that there are likely to be both positive impacts (for example, yield gains) and negative impacts (for example, increased water stress). Either way, there will be a need for new investments in adaptive management and technology, including new collaborations between the public and private sectors, to enable UK agriculture to respond to the potential effects of climate change